Expression of Lactate Dehydrogenase in Aspergillus niger for L-Lactic Acid Production. - Khyati K Dave; Narayan S Punekar (PLoS ONE, 2015)
Different engineered organisms have been used to produce L-lactate. Poor yields of lactate at low pH and expensive downstream processing remain as bottlenecks. Aspergillus niger is a prolific citrate producer and a remarkably acid tolerant fungus. Neither a functional lactate dehydrogenase (LDH) from nor lactate production by A. niger is reported. Its genome was also investigated for the presence of a functional ldh. The endogenous A. niger citrate synthase promoter relevant to A. niger acidogenic metabolism was employed to drive constitutive expression of mouse lactate dehydrogenase (mldhA). An appraisal of different branches of the A. niger pyruvate node guided the choice of mldhA for heterologous expression. A high copy number transformant C12 strain, displaying highest LDH specific activity, was analyzed under different growth conditions. The C12 strain produced 7.7 g/l of extracellular L-lactate from 60 g/l of glucose, in non-neutralizing minimal media. Significantly, lactate and citrate accumulated under two different growth conditions. Already an established acidogenic platform, A. niger now promises to be a valuable host for lactate production.